Character Education Based On Spiritual Quotient And Its Urgency In Macro Human Resource Development (Study Of Faculty Students Economics Of The Muslim Nusantara Al-Washliyah University) - Julianto Hutasuhut; Alkausar Saragih; Yayuk Yuliana (EDUTECH, 2020)
The background of research is phenomenon of the concept of education that too exalts intellectual quotient (IQ) rather than spiritual quotient (SQ). As a result, a shift can be seen that alienates people from their nature and more and more cases are complaining about the phenomenon of the world of work. The purpose of this study is to describe the character of spiritual quotient based character education at FE UMN Al-Washliyah and the urgency of developing human resources at a macro level. The research method used is descriptive statistical analysis with a quantitative approach. The population was students of FE UMN Al-Washliyah with a purposive sampling technique and a sample of 165 people. Research instrument using a questionnaire with a Likert scale measurement. Data analysis techniques use statistical descriptions of frequency and mean  and interpreted with four specific criteria. Test results: 1). The implementation of character education at FE UMN Al-Washliyah has a mean value of 3.21 and belongs to the good category. 2). The program to increase the spiritual quotient of students has a mean value of 3.40 and belongs to the very good category. 3). Human Resource Development through the Surah Ash Shaff civilization program: 10-11 at FE UMN Al-Washliyah went very well. This is related to the success of the character education program through spiritual quotient which has also been going well. Thus, this potential must be exploited more effectively so that achieving the vision is more beneficial for the advancement of education and social development